Antioxidant and enzyme-inhibiting activity of lyophilized extract from Clinopodium vulgare L. (Lamiaceae) - Gazela Nassar-Eddin; Dimitrina Zheleva-Dimitrova; Nikolay Danchev; Rumyana Vitanska-Simeonova (Pensoft Publishers, 2021)
Clinopodium vulgare L. (Lamiaceae) was used in the traditional Bulgarian medicine for treatment of wounds, diabetes and gastric ulcers. The aim of the present study was to evaluate the antioxidant capacity of the extract (CVE) and fractions from C. vulgare (CV) using DPPH, ABTS and FRAP methods. Enzyme inhibitory activity against acetylcholinesterase, α-glucosidase and α-amylase was also investigated. Rosmarinic acid was used as a positive control. The fraction CV3 demonstrated the highest radical scavenging activity with IC50 values of 0.02 mg/ml (DPPH) and 0.0002 mg/ml (ABTS), as well as the strongest ferric reducing potential (FRAP) of 0.89 mM TE/mg dw. The crude aqueous-methanol extract of C. vulgare also showed high activity with IC50 values of 0.05 mg/ml (DPPH), 0.04 mg/ml (ABTS) and 0.89 mM TE/mg dw (FRAP). Moreover, CV3 demonstrated moderate α-glucosidase and α-amylase inhibitory potential.